Correlation of Inclusive Communication Strategy with the Formation of Teacher Role Identity in State Special Needs Schools in Gorontalo City - Sofra Andini R Hala; Dwi Ratnasari; Andi Subhan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Inclusive education requires teachers to implement effective communication strategies in the learning process for students with special needs. Inclusive communication strategies are a crucial factor in supporting the teachers' role identity formation as educators in an inclusive educational environment. This study aimed to find the correlation between inclusive communication strategies and the teachers' role identity formation in a State Special School in Gorontalo City. This study employed a quantitative approach with a correlational method. Data collection through questionnaires was conducted with 43 respondents, teachers at the State Special School in Gorontalo City. Data analysis was conducted using the Pearson Product-Moment correlation test and the coefficient of determination test in SPSS. The findings showed a strong and significant relationship between inclusive communication strategies and teachers' role identity formation in a State Special School in Gorontalo City.  It was evidenced by the correlation coefficient of 0.703 in the strong category and a significance value of 0.000 < 0.05. The coefficient of determination indicated an R-square of 0.494, meaning that inclusive communication strategies contributed 49.4% to teachers' role identity formation.  Factors outside the study influenced the remaining 50.6%. It means that the better the inclusive communication strategies implemented by teachers, the better the teachers' role identity formation in the context of inclusive education.